The Possible Role of Color Doppler and Pulse Wave Doppler Ultrasound in the Diagnosis of Cutaneous Lymphangioma Circumscriptum. Issue 1 (January 2020) - Sun, Yang; Su, Jing; Li, Shan-Shan; Cui, Li-Gang
Abstract : Abstract: Cutaneous lymphangioma circumscriptum (CLC) is an uncommon congenital lymphatic malformation. Its dermoscopic features have been reported, however, if blood has infiltrated the lacunas, a pink hue overwhelms the lacunar structures, rendering dermoscopic features indistinguishable. In addition, dermoscopy cannot assess the subcutaneous extent of the lesion before surgery. The high-frequency array transducer Sonography with a high-frequency transducer is excellent in its resolution to evaluate skin lesions and is unaffected by infiltration of blood. Here, the authors report the use of ultrasound (color Doppler and pulse wave Doppler) for the diagnosis and management of CLC. An 18-year-old man presented 10 years previously with an asymptomatic 0.5 × 0.7 cm cluster of dark reddish vesicular lesions on his buttock. The lesions had recently increased in size and number. There was associated pachyderma. The lesions were hyperechoic and well defined on grayscale ultrasound and hypervascular on color Doppler ultrasound. Cluster cystics of lymphatic spaces were found throughout the whole dermis, especially in the papillary dermis. The lymphatic channels extended downwards to the reticular dermis and the superficial layer of the subcutaneous tissue. The pathological findings revealed lymphangiomas invading the subcutaneous tissue. The flat endothelial cells were partly positive for D2-40, which is a marker of lymphatic endothelial cells. Ultrasound was able to delineate the margins of the lesions. Diagnosis of CLC using preoperative color Doppler and pulse wave Doppler could reduce unnecessary repeated pre- and postoperative biopsies.